Preliminary observations on MRI correlates of driving independence and performance in persons with heart failure. (1st June 2015) - Alosco, Michael L.; Penn, Marc S.; Brickman, Adam M.; Spitznagel, Mary Beth; Cleveland, Mary Jo; Griffith, Erica Y.; Narkhede, Atul; Gunstad, John
<x xml:space="preserve">Abstract</x> Purpose/Aim: Heart failure patients often require assistance with activities of daily living, including driving. Recent work shows heart failure patients commit more errors on a simulated driving task relative to controls and cognitive dysfunction contributed to these errors. We sought to extend these findings by examining whether structural magnetic resonance imaging indices correlate with driving independence and performance in heart failure. Materials and Methods: Forty-nine heart failure patients underwent brain magnetic resonance imaging and performed a battery assessing attention/executive function and memory. A self-report instrument was used to assess independence in transportation. A subset of heart failure participants (N = 8) completed a validated driving simulator scenario. Results: Among the larger sample (N = 49), reduced gray matter correlated with greater dependence in transportation and worse attention/executive function; in turn, worse attention/executive function predicted greater assistance with transportation (p < 0.05). Among the subset that completed the driving simulator (N = 8), reduced gray matter correlated with more stop signs missed and increased white matter hyperintensities correlated with greater collisions, centerline crossings and time out of lane (p < 0.05). Poorer attention/executive function was also associated with more time over the speed limit on the driving simulation (p < 0.05). Follow-up analyses showed the above effects were largely independent of age. Conclusions: Reduced structural brain integrity is associated with poorer reported and simulated driving in persons with heart failure. Larger prospective studies that employ on-road testing are needed to clarify brain changes and risk for unsafe driving in heart failure.